Análisis de los transcritos del gen fusión bcr-abl relacionados con la leucemia mieloide crónica mediante las técnicas de rt-pcr y electroforesis capilar - Proaño Rubio, Kimberly Naomi (2019)
Leukemia is a type of cancer that appears in the primitive cells of the bone marrow responsible for blood renewal. Chronic myeloid leukemia (CML) is a chronic myeloproliferative syndrome that is originated in a pluripotent stem cell present in the three hematopoietic series. It is also one of the four main types of leukemia. This pathology results from a genetic exchange between chromosomes 9 and 22, giving rise to a chimeric gene BCR-ABL, where three types of transcripts may be presented, depending on the breakpoint in the BCR gene. The objective of this research consists in analyze the different transcripts of the BCR-ABL fusion gene in Ecuadorian patients with CML and report the results obtained for each transcript. To achieve this objective, 35 RNA samples from patients with a positive diagnosis for BCR-ABL were studied by RT-PCR and capillary electrophoresis. The results obtained after the optimization of the techniques is that the b3a2 transcript is the most frequent, occurring in 60 percent of the patients, followed by the b2a2 transcript with 28.75 percent and finally the coexpression between b2a2 b3a2 with 17.14 percent. The frequencies reported in this study were compared with the world frequencies, and found out that there are no differences. However, the frequencies obtained do not coincide with the frequencies previously reported in Ecuador.